2019
DOI: 10.1007/s00405-019-05469-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of hyperbaric oxygen therapy in acute hearing loss: a narrative review

Abstract: Introduction Acute hearing loss can have a major impact on a patient’s life. This holds true for both acute acoustic trauma (AAT) and idiopathic sudden sensorineural hearing loss (ISSHL), two devastating conditions for which no highly effective treatment options exist. This narrative review provides the rationale and evidence for HBOT in AAT and ISSHL. Methods Narrative review of all the literature available on HBOT in acute hearing loss, studies were retrieved from sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 128 publications
(132 reference statements)
0
31
0
1
Order By: Relevance
“…There are many reports that HBO therapy has beneficial effects for the treatment of ISSHL [6,10,12,17]. Recent studies have also shown that addition of HBO to corticosteroid treatment may be beneficial in both acute acoustic trauma and ISSHL, especially when initiated early [18]. It was reported that HBO therapy was found to cause a significant improvement in PTA thresholds in ISSHL cases where primary corticosteroid therapy failed and were within 4 weeks of onset of hearing loss [17].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports that HBO therapy has beneficial effects for the treatment of ISSHL [6,10,12,17]. Recent studies have also shown that addition of HBO to corticosteroid treatment may be beneficial in both acute acoustic trauma and ISSHL, especially when initiated early [18]. It was reported that HBO therapy was found to cause a significant improvement in PTA thresholds in ISSHL cases where primary corticosteroid therapy failed and were within 4 weeks of onset of hearing loss [17].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, HBOT is highly efficacious in the treatment of several conditions spanning a broad pathological range [ 19 ]. Actual European indications for the medical use of HBOT were established during the ECHM Consensus Conference in 2016, taking into account three types of recommendations for using HBOT as a medical procedure—from strongly recommended to optional use, depending on the strength of the evidence of its beneficial action [ 2 ].…”
Section: The Use Of Hyperbaric Oxygenation In Medicinementioning
confidence: 99%
“…This illness is considered to be a true otologic emergency [ 23 ]. For smaller losses, some patients regain their pre-loss hearing threshold without medical therapy due to the repair capacity of the cochlea, but in cases of profound hearing impairment the chance of complete recovery is limited [ 19 ]. The majority (about 90%) of SSNHL cases is idiopathic and several causes have been proposed to explain its etiopathogenesis (i.e., viral infection, otologic disease, trauma, vascular causes, and neoplastic disease, in order from the most frequent to rare [ 24 ].…”
Section: Hbot In the Treatment Of Sudden Sensorineural Hearing Losmentioning
confidence: 99%
“…It is suggested that ischemia due to vascular damage is involved in developing SSNHL. Thereby, it is assumed that ischemia-induced impaired hearing will be improved with HBOT by increasing the availability of oxygen in the inner ear [6][7]. Although the HBOT for SSNHL is suggested within two weeks of the onset of the disease, HBOT can also be suggested as salvage therapy within one month of onset of SSNHL [5].…”
Section: Introductionmentioning
confidence: 99%